Science, religion, and nonreligion: Engaging subdisciplines to move further beyond mythbusting. (February 2023) - Catto, Rebecca; Riley, James; Elsdon-Baker, Fern; Jones, Stephen H.; Leicht, Carola
Within the last 20 years sociological research on science and religion has provided new insights that challenge myths regarding conflicts between science and religion. Gaps in pre-existing work have been identified resulting in major shifts in the field. In particular, research has employed more mixed methods, widened its scope to become more international, and expanded to include nonreligion. Building upon these developments and critiques, this chiefly conceptual article explores a way to move forward by combining three fields of research in a novel way: the sociology of religion, the sociology of nonreligion, and the Public Understanding of Science (PUS). These subfields all touch on relevant and interrelated topics. Sociology of religion contributes to parceling out aspects of belief, identity, and practice; focuses on lived experience along with positionality, normative commitments, and culture. The sociology of nonreligion draws more detailed attention to the association between science and secularism. Finally, including research on PUS provides resources for understanding trust in, and engagement with science dialogically, as well as lessons for effective public engagement.